The silent language of connection: Nonverbal rituals in intercultural friendships at a Chinese university - Anjum, Syed Waqas; Jinquan, Wang; Fu, Weinian; Ye, Zhuoqi (Journal of International Students, 2025)
This study examines how international and Chinese students at a Chinese university form intercultural friendships through nonverbal rituals, including silence, gift-giving, and shared meals. Using a qualitative ethnographic approach, the study draws on 50 interviews, six focus groups, and 120 hours of observation. The findings reveal that silence serves to manage emotions and maintain face, gift-giving acts as a nonverbal apology and connector, and shared meals create hybrid cultural spaces for mutual understanding. These nonverbal practices enable students to develop trust and resolve conflicts without relying on language. The study contributes to the development of intercultural competence by extending symbolic interactionism to encompass nonverbal communication and reinterpreting face negotiation theory through the lens of embodied interaction. The research introduces the concept of “third culture building,” suggesting that student-driven rituals are essential for fostering inclusive environments in higher education. The findings highlight the importance of informal interactions in cultivating intercultural relationships.